THE REALITY OF SHOP RENTAL PRICES AND TENANTS’ INCOME CAPACITY IN IJᾹRAH ‘ALᾹ AL-MANᾹFI’ AGREEMENTS IN BANDA ACEH - Aklil Muyassar; Safira Mustaqilla (Al-Mudharabah: Jurnal Ekonomi dan Keuangan Syariah, 2026)
This study aims to analyse the reality of shop rental pricing and its suitability to tenants’ income capacity from the perspective of ijārah ‘ala al-manāfi’ contracts in Banda Aceh City. The practice of renting shops in strategic locations has led to a significant upward trend in rental prices, often set unilaterally, creating an imbalance between rental costs and the sustainability of tenants’ businesses. This study is an empirical legal study that uses a case study and a conceptual approach. Data was obtained through interviews with tenants and shop owners directly involved in rental practices, supported by a review of relevant fiqh muamalah literature. The results show that shop rental prices in Banda Aceh are generally determined by location and market demand, but are often set without a clear written contract specifying the terms and mechanism for rent increases. Rent increases were found to be unilateral and disproportionate to tenants’ income capacity, causing an imbalance between rental costs and business profits. This practice contributes to the decline in tenants’ business stability, hindering long-term planning and increasing the risk of losses and business relocation. This study concludes that shop rental practices in Banda Aceh are not yet fully in accordance with the principles of ijārah ‘ala al-manāfi’, particularly those related to willingness (tarāḍin), fairness, transparency, and benefit. There is a need to formulate clearer and fairer rental agreements so that the mechanism for determining rental prices does not disadvantage either party and is in line with the principles of Islamic economic law.